Work Motivation of Staff as a Factor in Improving Financial Performance of a Commercial Enterprise - О. A. Vasilenko (Финансы: теория и практика, 2019)
Effective functioning of any organization is based on a seamless blend of the interaction between a person and organization. The importance of various types of work motivation aimed at achieving the goals of the organization and encouraging staff to work effectively determined the relevance of the study. The purpose of the study is to find ways to improve the system of work motivation, on the example of a particular enterprise, and to develop recommendations for improving the performance of the enterprise based on a motivational mechanism. The research objectives are the following: to analyze the current system of work motivation, to assess the efficiency of labor resources at the enterprise, to develop proposals for improving the financial performance of the enterprise through the motivational mechanism. The object of the study is the staff of OOO KL GROUP company specializing in retail trade of footwear, clothing and other products made of genuine leather. The subject of the study is the system of work motivation of staff and financial performance of the company. The following methods were used in the work: comparison, monographic, economic and statistical, horizontal and vertical analysis, expert assessment, sociology, organization theory and others. The authors used the results of a survey conducted by the territorial managers of the company in ten sales departments in order to identify the intensity of customer flows and the time-management of the company employees. A systematic approach in studying motivation factors allowed to develop proposals for creating a system of staff motivation at the enterprise. It is concluded that the implementation of the work motivation mechanism in the sales departments of OOO KL GROUP company gives the following results: satisfaction with the employees and their activities increases, and the company receives an annual increase in profits. Thus, work motivation affects the financial performance of the company.